The effect of phenytoin on the proliferative ability of periodontal and gingival ligament fibroblasts in cell culture medium: Phenytoin on gingival fibroblasts and PDL cells - Zhang, Li; Gao, Qi; Peng, Xuezhen; Deng, Shuman; Zhang, Li (Cellular and Molecular Biology, 2022)
Periodontal ligament fibroblasts (PDLFs) play a vital role in the period of periodontal regeneration. In addition, studies show that diphenylhydantoin (phenytoin) increases the growth of gingival fibroblasts. If this effect is also present in the periodontal ligament (PDL) fibroblasts, it may be used to regenerate periodontal tissues. Accordingly, this study aimed to compare the effect of phenytoin on the growth rate of gingival fibroblast cells and PDL in the cell culture medium. In this regard, 10 Wistar rats were selected. The gingival specimen was obtained from the area between the upper teeth, and the PDL specimen was obtained from the middle third of the lower teeth root. After transferring the samples to a suitable culture medium for culturing PDL and gingival fibroblasts, each sample was divided into two experimental and control groups. In the experimental group, 20 mg/ml phenytoin dissolved in sodium hydroxide was added to Dulbecco’s modified Eagle’s medium (DMEM). After 48 hours, fibroblast cell proliferation was assessed through a 1-WST cell proliferation kit by ELISA. The proliferation of gingival fibroblast cells and PDL in both test and control groups were statistically analyzed by the independent t-test. The results showed that the effect of phenytoin on the proliferation of gingival fibroblast cells and PDL fibroblast cells is significant. Also, the proliferation of PDL cells was significantly different from gingival cells in the experimental group (P <0.001) and was higher in PDL cells. In general, in this study, it was found that phenytoin in vitro, like in vivo, is able to increase the proliferation of gingival fibroblast cells, and this phenytoin effect is also present in PDL fibroblast cells.